Interface application development for a Keithley 6517B electrometer using LabVIEW programming to measure resistance and temperature as functions of time - Ahmed, Arik Rafiquddin (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2016.